Effects of Open Skill Visuomotor Choice Reaction Time Training on Unanticipated Jump-Landing Stability and Quality: A Randomized Controlled Trial - Friebe, David; Engeroff, Tobias; Giesche, Florian; Niederer, Daniel (Frontiers in Human Neuroscience, 2021)
Adapting movements rapidly to unanticipated external stimuli is paramount for athletic performance and to prevent injuries. We investigated the effects of a 4-week open-skill choice-reaction training intervention on unanticipated jump-landings. Physically active adults (n = 37; mean age 27, standard deviation 2.7 years, 16 females, 21 males) were randomly allocated to one of two interventions or a control group (CG). Participants in the two intervention groups performed a 4-week visuomotor open skill choice reaction training, one for the upper and one for the lower extremities. Before and after the intervention, two different types of countermovement jumps with landings in split stance position were performed. In the (1) pre-planned condition, we informed the participants regarding the landing position (left or right foot in front position) before the jump. In the (2) unanticipated condition, this information was displayed after take-off (350–600 ms reaction time before landing). Outcomes were landing stability [peak vertical ground reaction force (pGRF) and time to stabilization (TTS)], and landing-related decision-making quality (measured by the number of landing errors). To measure extremity-specific effects, we documented the number of correct hits during the trained drills. A two-factorial (four repeated measures: two conditions, two time factors; three groups) ANCOVA was carried out; conditions = unanticipated versus pre-planned condition, time factors = pre versus post measurement, grouping variable = intervention allocation, co-variates = jumping time and self-report arousal. The training improved performance over the intervention period (upper extremity group: mean of correct choice reaction hits during 5 s drill: +3.0 hits, 95% confidence interval: 2.2–3.9 hits; lower extremity group: +1.6 hits, 0.6–2.6 hits). For pGRF (F = 8.4, p < 0.001) and landing errors (F = 17.1, p < 0.001) repeated measures effect occurred. Significantly more landing errors occurred within the unanticipated condition for all groups and measurement days. The effect in pGRF is mostly impacted by between-condition differences in the CG. No between-group or interaction effect was seen for these outcomes: pGRF (F = 0.4, p = 0.9; F = 2.3, p = 0.1) landing errors (F = 0.5, p = 0.6; F = 2.3, p = 0.1). TTS displayed a repeated measures (F = 4.9, p < 0.001, worse values under the unanticipated condition, improvement over time) and an interaction effect (F = 2.4, p = 0.03). Healthy adults can improve their choice reaction task performance by training. As almost no transfer to unanticipated landing successfulness or movement quality occurred, the effect seems to be task-specific. Lower-extremity reactions to unanticipated stimuli may be improved by more specific training regimens.